Breath work: visualizing the invisible and relational breath. (3rd April 2019) - Fahd, Cherine
ABSTRACT: In this paper I explore the significance of the breath in contemporary art. While breathing operates at the margins of perception, its symbolic possibilities are frequently visualized in photography, video and performance-based works. I catalyse Allan Kaprow's instructive breathing piece, Performing Life (1979), to open up a perspective on the corporeal, creative and inter-subjective dimension of the breath in the work of Australian artists Julie Rrap, Daniel Mudie Cunningham and the late Australian/Italian artist Katthy Cavaliere. These artists, via a diversity of means, perform breathing and inadvertently achieve Kaprow's intention of drawing attention to what is overlooked in everyday life. I examine how Rrap, Cunningham and Cavaliere's works induce a consciousness of the breath in the viewer. Further, I have undertaken this examination by reflecting on the unavoidable connection between breathing and death. This discussion brings important detail to embodied spectatorship whereby 'breath work' is viewed as engendering an awareness of embodied subjectivity, creativity and community.